Genetic and genomic evidence of niche partitioning and adaptive radiation in mountain pine beetle fungal symbionts - Dario I. Ojeda Alayon; Clement K. M. Tsui; Nicolas Feau; Arnaud Capron; Braham Dhillon; Yiyuan Zhang; Sepideh Massoumi Alamouti; Celia K. Boone; Allan L. Carroll; Janice E. K. Cooke; Amanda D. Roe; Felix A. H. Sperling; et al. (Molecular Ecology, 2017)
Bark beetles form multipartite symbiotic associations with blue stain fungi (Ophiostomatales, Ascomycota). These fungal symbionts play an important role during the beetle's life cycle by providing nutritional supplementation, overcoming tree defences and modifying host tissues to favour brood development. The maintenance of stable multipartite symbioses with seemingly less competitive symbionts in similar habitats is of fundamental interest to ecology and evolution. We tested the hypothesis that the coexistence of three fungal species associated with the mountain pine beetle is the result of niche partitioning and adaptive radiation using SNP genotyping coupled with genotype–environment association analysis and phenotypic characterization of growth rate under different temperatures. We found that genetic variation and population structure within each species is best explained by distinct spatial and environmental variables. We observed both common (temperature seasonality and the host species) and distinct (drought, cold stress, precipitation) environmental and spatial factors that shaped the genomes of these fungi resulting in contrasting outcomes. Phenotypic intraspecific variations in Grosmannia clavigera and Leptographium longiclavatum , together with high heritability, suggest potential for adaptive selection in these species. By contrast, Ophiostoma montium displayed narrower intraspecific variation but greater tolerance to extreme high temperatures. Our study highlights unique phenotypic and genotypic characteristics in these symbionts that are consistent with our hypothesis. By maintaining this multipartite relationship, the bark beetles have a greater likelihood of obtaining the benefits afforded by the fungi and reduce the risk of being left aposymbiotic. Complementarity among species could facilitate colonization of new habitats and survival under adverse conditions.

Population structure and migration pattern of a conifer pathogen, Grosmannia clavigera , as influenced by its symbiont, the mountain pine beetle - CLEMENT K. M. TSUI; AMANDA D. ROE; YOUSRY A. EL‐KASSABY; ADRIANNE V. RICE; SEPIDEH M. ALAMOUTI; FELIX A. H. SPERLING; JANICE E. K. COOKE; JÖRG BOHLMANN; RICHARD C. HAMELIN (Molecular Ecology, 2012)
We investigated the population structure of Grosmannia clavigera (Gc), a fungal symbiont of the mountain pine beetle (MPB) that plays a crucial role in the establishment and reproductive success of this pathogen. This insect–fungal complex has destroyed over 16 million ha of lodgepole pine forests in Canada, the largest MPB epidemic in recorded history. During this current epidemic, MPB has expanded its range beyond historically recorded boundaries, both northward and eastward, and has now reached the jack pine of Alberta, potentially threatening the Canadian boreal forest. To better understand the dynamics between the beetle and its fungal symbiont, we sampled 19 populations in western North America and genotyped individuals from these populations with eight microsatellite markers. The fungus displayed high haplotype diversity, with over 250 unique haplotypes observed in 335 single spore isolates. Linkage equilibria in 13 of the 19 populations suggested that the fungus reproduces sexually. Bayesian clustering and distance analyses identified four genetic clusters that corresponded to four major geographical regions, which suggested that the epidemic arose from multiple geographical sources. A genetic cluster north of the Rocky Mountains, where the MPB has recently become established, experienced a population bottleneck, probably as a result of the recent range expansion. The two genetic clusters located north and west of the Rocky Mountains contained many fungal isolates admixed from all populations, possibly due to the massive movement of MPB during the epidemic. The general agreement in north–south differentiation of MPB and G. clavigera populations points to the fungal pathogen’s dependence on the movement of its insect vector. In addition, the patterns of diversity and the individual assignment tests of the fungal associate suggest that migration across the Rocky Mountains occurred via a northeastern corridor, in accordance with meteorological patterns and observation of MPB movement data. Our results highlight the potential of this pathogen for both expansion and sexual reproduction, and also identify some possible barriers to gene flow. Understanding the ecological and evolutionary dynamics of this fungus–beetle association is important for the modelling and prediction of MPB epidemics.

Gene genealogies reveal cryptic species and host preferences for the pine fungal pathogen Grosmannia clavigera - SEPIDEH M. ALAMOUTI; VINCENT WANG; SCOTT DiGUISTINI; DIANA L. SIX; JÖRG BOHLMANN; RICHARD C. HAMELIN; NICOLAS FEAU; COLETTE BREUIL (Molecular Ecology, 2011)
Grosmannia clavigera is a fungal pathogen of pine forests in western North America and a symbiotic associate of two sister bark beetles: Dendroctonus ponderosae and D. jeffreyi . This fungus and its beetle associate D. ponderosae are expanding in large epidemics in western North America. Using the fungal genome sequence and gene annotations, we assessed whether fungal isolates from the two beetles inhabiting different species of pine in epidemic regions of western Canada and the USA, as well as in localized populations outside of the current epidemic, represent different genetic lineages. We characterized nucleotide variations in 67 genomic regions and selected 15 for the phylogenetic analysis. Using concordance of gene genealogies and distinct ecological characteristics, we identified two sibling phylogenetic species: Gc and Gs. Where the closely related Pinus ponderosa and P. jeffreyi are infested by localized populations of their respective beetles, Gc is present. In contrast, Gs is an exclusive associate of D. ponderosae mainly present on its primary host‐tree P. contorta ; however, in the current epidemic areas, it is also found in other pine species. These results suggest that the host‐tree species and the beetle population dynamics may be important factors associated with the genetic divergence and diversity of fungal partners in the beetle‐tree ecosystems. Gc represents the original G. clavigera holotype, and Gs should be described as a new species.

Ophiostomatoid fungi associated with the northern spruce engraver, Ips perturbatus, in western Canada - Sepideh Massoumi Alamouti; Jae-Jin Kim; Leland M. Humble; Adnan Uzunovic; Colette Breuil (Antonie van Leeuwenhoek, 2006)